A new strategy to prepare giant vesicles from surface active ionic liquids (SAILs): a study of protein dynamics in a crowded environment using a fluorescence correlation spectroscopic technique. Issue 21 (13th May 2016) - Banerjee, Chiranjib; Roy, Arpita; Kundu, Niloy; Banik, Debasis; Sarkar, Nilmoni
Abstract : A simple procedure for the preparation of giant vesicles using surface active ionic liquids (SAILs) has been provided in this paper. Abstract : A simple procedure for the preparation of giant vesicles using surface active ionic liquids (SAILs) has been provided in this paper. SAILs, used to form vesicles, were synthesized by replacing the cationic part of Aerosol OT (AOT) with cations having alkyl chains of different lengths (ammonium and imidazolium cations). The number of carbons in the alkyl chains of the cations was varied from eight to sixteen. From the observed results, the formation of giant vesicles is found to be dependent on the alkyl chain length as well as the organic moieties of the respective cations. These giant vesicles were characterized using fluorescence lifetime imaging microscopy (FLIM). The conformational dynamics of bovine serum albumin (BSA) inside these giant vesicles was determined using fluorescence correlation spectroscopy (FCS) to get an idea about the protein dynamics in a constrained environment. The interaction of the giant vesicles with the protein was confirmed by the change in the diffusion coefficient and the conformational fluctuation time.